Kesalahan Penggunaan Kata Hubung dalam Karangan Deskripsi pada Siswa Kelas X SMA Perintis 2 Bandar Lampung - Riska Alfiawati; Destia Herlisya (LPPM STKIP PGRI Bandar Lampung, 2023)
This research aims to describe and analyze the level of student ability in using conjunctions in descriptive essays for class add references to books in the school library, especially those related to the use of descriptive essays. The problem raised in this research is the ability to use conjunctions in descriptive essays in class X even semester students at SMA Perintis 2 Bandar Lampung. To achieve the research objectives mentioned above, the author uses a descriptive method, namely by analyzing the accuracy of the use of conjunctions in descriptive essays written by students, calculating and percentageing the level of student mastery in using conjunctions in descriptive essays based on the rules for using conjunctions well and correctly. The results of the research show that students' mastery of using conjunctions in descriptive essays is relatively poor.